INTERACTION OF DOSAGE AND SPRAY FREQUENCY OF HENNA (Lawsonia inermis) LEAF EXTRACTS IN THE MANAGEMENT OF ALTERNARIA LEAF SPOT DISEASE OF CUCUMBER (Cucumis sativus L.) IN MAIDUGURI, NIGERIA - Mohammed, Z. H.; Bwala, R. I.; Tata, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2022)
Field trial was conducted in 2018 and 2019 cropping seasons at Teaching and Research Farm of the Faculty of Agriculture, University of Maiduguri to assess the effects of the interaction of dosage and spray frequency of Lawsonia inermis leaf extracts in the management of Alternaria leaf spot disease of cucumber in Maiduguri. The treatments consisted of three Dosages (50g/L, 75g/L and 100g/L) assigned as a Vertical factor and five spray regimes (no spray, spray once, spray twice, spray thrice and four times) as a horizontal factor, factorially combined and laid out in a split plot design with three replications. Results of the experiment showed that, interaction of the spray frequency (three or four times) and dosage (100g/L) of the leaf extracts significantly reduced disease incidence and severity of Alternaria leaf spot disease better than the other treatment combinations. The result further revealed a significantly higher yield increase under the same condition than the other treatments considered. Based on the result of this findings, it can be concluded that spraying of cucumber three or four times coinciding with the fruiting stage of the crop were important in reduction of the disease.